Longevity Relatives Count score identifies heritable longevity carriers and suggests case improvement in genetic studies. Issue 6 (30th April 2020) - van den Berg, Niels; Rodríguez‐Girondo, Mar; Mandemakers, Kees; Janssens, Angelique A. P. O.; Beekman, Marian; Slagboom, P. Eline
Abstract: Loci associated with longevity are likely to harbor genes coding for key players of molecular pathways involved in a lifelong decreased mortality and decreased/compressed morbidity. However, identifying such loci is challenging. One of the most plausible reasons is the uncertainty in defining long‐lived cases with the heritable longevity trait among long‐living phenocopies. To avoid phenocopies, family selection scores have been constructed, but these have not yet been adopted as state of the art in longevity research. Here, we aim to identify individuals with the heritable longevity trait by using current insights and a novel family score based on these insights. We use a unique dataset connecting living study participants to their deceased ancestors covering 37, 825 persons from 1, 326 five‐generational families, living between 1788 and 2019. Our main finding suggests that longevity is transmitted for at least two subsequent generations only when at least 20% of all relatives are long‐lived. This proves the importance of family data to avoid phenocopies in genetic studies. Abstract : In this study we show that human longevity is transmitted for at least 2 subsequent generations only when at least 20% of a person's relatives are long‐lived. The analyses are based on a unique dataset, covering 37, 825 persons from 1, 326 five‐generational families, in which living study participants are connected to their deceased ancestors. Our findings highlight the importance of using survival information of relatives/ancestors to avoid long‐lived phenocopies in genetic studies and aim to stimulate cohort studies to extend their data with such ancestral information.